2020
DOI: 10.3390/jcm9072187
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Polyetheretherketone (PEEK)–Acrylic Resin Prostheses and the All-on-4 Concept: A Full-Arch Implant-Supported Fixed Solution with 3 Years of Follow-Up

Abstract: Background: The aim of this three-year prospective study was to examine the outcome of a solution for full-arch rehabilitation through a fixed implant-supported hybrid prosthesis (polyetheretherketone (PEEK)-acrylic resin) used in conjunction with the All-on-4 concept. Methods: Thirty-seven patients (29 females, 8 males), with an age range of 38 to 78 years (average: 59.8 years) were rehabilitated with 49 full-arch implant-supported prostheses (12 maxillary rehabilitations, 13 mandibular rehabilitations and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 52 publications
5
46
0
1
Order By: Relevance
“…This is an advantage compared to rigid metallic frames. In line with our finding, Nobre et al 15 noted that prosthetic survival was influenced by the state of the opposing jaw and prosthetic failure occluded in patients rehabilitated by All on four concept in the upper and lower jaw with bruxism that caused a framework fracture, which suggest occlusal overload.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is an advantage compared to rigid metallic frames. In line with our finding, Nobre et al 15 noted that prosthetic survival was influenced by the state of the opposing jaw and prosthetic failure occluded in patients rehabilitated by All on four concept in the upper and lower jaw with bruxism that caused a framework fracture, which suggest occlusal overload.…”
Section: Discussionsupporting
confidence: 91%
“…In this study we reported no acrylic resin fracture from the PEEK frame. The difference in the results may be due to in the study of Nobre et al 15 , the majority of the Prostheses contained more than one cantilevered teeth rendering technical complications (veneer adhesion issues) more common due to flexing of the PEEK framework distal cantilever. However, in this study no cantilevers or maximum one tooth cantilever was used.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations